(untitled) (Bangladesh Medical Journal, 2014)
Atopic dermatitis (AD) is a genetically determined itchy inflammatory condition characterized by poorly defined erythema with edema, vesicles and weeping in the acute stage and skin thickenings in the chronic stage with a predilection for skin flexures. Atopic dermatitis is the most frequent type of chronic eczema associated with severe pruritus which may lead to constant scratching, producing excoriations and lichenification. There is no single distinguishing feature of AD or a diagnostic laboratory test. Hanifin and Rajka proposed a number of clinical sign and symptoms to define diagnosis of AD. The diagnosis requires the presence of at least three major features and at least three minor features. This clinical study is intended to find out the most frequent sign and symptom of AD. Fifty patients were elected as AD according to Hanifin and Rajka criteria in out patient department of Dermatology and Venereology of Dhaka Medical College Hospital. Majority of the study subjects (39%) were between 10-19 years and most of them were male (54%). The mean duration of AD was 8.9 (±8.1) years. Regarding occupation 36% were student. Twenty four (24) percent of patient had family history of asthma and 14% had allergic rhinitis. Around 36% cases had personal history of allergic rhinitis and 18% had asthma. The most frequent symptoms were itch when sweating (56%) followed by intolerance of food (36%) and disease influenced by environmental and emotional factors (22%). Among the signs most common were flexural lichenification (96%) followed by xerosis (76%), cheilitis (52%), ichthyosis/hyperlinear palms (24%), extensor involvement and orbital darkening were 22% each, non-specific hand & foot eczema (18%) and pityriasis alba (16%.) DOI: http://dx.doi.org/10.3329/bmj.v42i1.18973 Bangladesh Med J. 2013 Jan; 42 (1): 18-20